2009
DOI: 10.1111/j.1365-313x.2009.03877.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ABA‐INSENSITIVE (ABI) 4 factor acts as a central transcription activator of the expression of its own gene, and for the induction of ABI5 and SBE2.2 genes during sugar signaling

Abstract: SUMMARYThe transcription factor ABA INSENSITIVE 4 (ABI4), discovered nearly 10 years ago, plays a central role in a variety of functions in plants, including sugar responses. However, not until very recently has its mechanism of action begun to be elucidated. Modulating gene expression is one of the primary mechanisms of sugar regulation in plants. Nevertheless, the transcription factors involved in regulating sugar responses and their role(s) during the signal transduction cascade remain poorly defined. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 74 publications
6
162
0
Order By: Relevance
“…16 It was argued that ABI4 expression is limited to seed maturation and to a few days following germination. 15,18,20 On the other hand, ABI4 was reported to be expressed in shoots and roots of three-week-old plants. 7 Furthermore, we recently showed, both quantitatively and histologically, that ABI4 is expressed in mature regions of the roots at later developmental stages and that its steady-state levels are enhanced by ABA and cytokinin and reduced by auxin.…”
Section: Abi4 Expression Datamentioning
confidence: 99%
See 2 more Smart Citations
“…16 It was argued that ABI4 expression is limited to seed maturation and to a few days following germination. 15,18,20 On the other hand, ABI4 was reported to be expressed in shoots and roots of three-week-old plants. 7 Furthermore, we recently showed, both quantitatively and histologically, that ABI4 is expressed in mature regions of the roots at later developmental stages and that its steady-state levels are enhanced by ABA and cytokinin and reduced by auxin.…”
Section: Abi4 Expression Datamentioning
confidence: 99%
“…At these stages, ABI4 was shown to be involved in glucose signaling, 12,14,16,17 sugar signaling and response pathways, 11,13,18 ABA signaling 3,[11][12][13]15 and lipid mobilization in the embryo and germinating seeds, 21,22 as well as in chloroplast functioning and retrograde signaling. 20,23 Other studies, using older plants, showed that ABI4 is involved in nitratemodulated root branching, 24 sugar insensitivity in fully expanded leaves, 25 responses to plant pathogens and tolerance to β-amino-butyric acid (BABA)-induced water stress, [26][27][28][29] mitochondrial retrograde signaling, 30 chloroplast photosynthesis, 31,32 and modulation of hormonal control of at this developmental stage.…”
Section: Proposed Biological Roles For Abi4mentioning
confidence: 99%
See 1 more Smart Citation
“…ABI4 is known to bind to the ABI5 promoter and enhance its expression 33 . This information prompted us to test whether MED18 directly interacts with ABI4 to regulate ABI5 gene expression.…”
Section: Med18 Contributes To Plant Defence Against Necrotrophsmentioning
confidence: 99%
“…6C). GUS was expressed in the cotyledons, hypocotyls, and root tips of 60-50 7-d-old Col-0 seedlings, in accordance with the expression pattern of ABI4 (Bossi et al, 2009). On 0.1 mM N, GUS expression levels increased in cotyledons and hypocotyls.…”
Section: Abi4 Binds To the Ce1-like Elements In The Dgat1 Promotermentioning
confidence: 99%